Digital Innovation in the Transformation of BPR: Building a Sustainable Financial Ecosystem in the Era of Disruption - Annisa Fitriah Mudassir; Muhammad Khaidir Kahfi Natsir (SEULANGA SYSTEM PUBLISHER, 2025)
In the continuously evolving digital era, the financial sector, particularly Rural Credit Banks (BPR), faces significant new challenges and opportunities. Digital transformation is not merely a trend but an urgent necessity to ensure the sustainability and competitiveness of financial institutions amid technological disruptions. The research method used is a qualitative approach with literature study techniques, involving data analysis from various sources, including official documents, scientific articles, and observations of BPR practices in the field. The results indicate that digitalization can significantly improve the operational efficiency of BPR, expand access to financial services for the community, and build an inclusive and sustainable financial ecosystem. Digital innovations, such as the development of mobile banking applications and the use of analytical technology, enable BPR to reach segments of society that were previously underserved by formal financial institutions. However, despite the great potential offered by digital innovations, many BPR still face various challenges in their implementation. This research identifies several key barriers, including a lack of understanding of technology among management and staff, inadequate information technology infrastructure, and regulatory challenges that hinder the adoption of new technologies. Additionally, findings highlight the importance of training and skill development for BPR employees to adapt to rapid digital changes. This research also emphasizes the need for collaboration between BPR and financial technology (fintech) companies and other institutions to create a mutually supportive ecosystem. Through this cooperation, BPR can leverage existing innovations to enhance service quality and expand market reach. The results of this study are expected to contribute significantly to the understanding and practice of digital innovation in the financial sector, as well as serve as a reference for stakeholders, including regulators, academics, and practitioners in the financial field, in formulating policies and strategies that support the development of BPR in Indonesia.